Annual Plan 2002-03 Revised Outlay 2002-03 - Planning Commission (Planning Commission, 2002)
I am directed to refer to the Government of Andhra Pradesh’s letter No. 13130/PLG. XVIII/2002- 2 dated 22nd March, 2003 on the above subject and convey the acceptance of Planning Commission to the revised outlay of Rs.8553.19 crore subject to availability of resources. The revised scheme of financing the revised outlays, is given at Annexure. A statement Showing the distribution of revised plan outlay under different heads and subheads of development is enclosed. the earmarked outlays and outlays for different components of PMGY have also been indicated therein. This issues with the approval of competent authority. Kindly acknowledge receipt of this letter.
Planning Commission State Plan Division